New Structural Design of a Compliant Gripper Based on the Scott-Russell Mechanism. (9th December 2014) - Ai, Wenji; Xu, Qingsong
This paper presents the structural design and analysis of a novel compliant gripper based on the Scott-Russell (SR) mechanism. The SR mechanism in combination with a parallelogram mechanism enables the achievement of a pure translation of the gripper tips, which is attractive for practical micromanipulation and microassembly applications. Unlike traditional pure-translation grippers, the reported SR-based gripper exhibits a simple structure as well as compact dimension because the in-plane space is fully used. The kinematics, statics and dynamics models of the gripper mechanism are established, and finite element analysis (FEA) simulations are carried out to verify the structure design. A prototype has been developed for experimental testing. The results not only demonstrate the feasibility of the proposed SR-based gripper design but also reveal a promising performance of the gripper when driven by piezoelectric stack actuators. Moreover, several variations of the gripper structure are presented as well.